Konsep 'Sacred Space' dalam Arsitektur Gereja Katolik - Doni Srisadono, Yosef (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2012)
Liturgy is an essential part of the Catholic Church, because in the liturgy is celebrated the feast of faith as the foundation on which the Catholic Church has been established. The celebration of faith which is spiritual in its nature is carried on in a “physical container”, namely the architecture of the Catholic Church. Because the feast is a holy and sacred celebration, the “physical container” should also be a “sacred space” that it becomes essential as well to create an architectural work with sacred space that can accommodate the holy celebration. This paper wants to explore the theological and liturgical meaning of the concept of sacred space in the Catholic Church architecture. This understanding might be important for those who have particular concern for the Catholic Church architecture, which lately seems to suffer desacralisation in the context and appearance of its architecture.